Association between sarcopenia and functional outcomes after bipolar hemiarthroplasty in elderly patients with displaced femoral neck fracture: Structural equation modeling - Artykbay, Sanzhar; J. Kerr, Stephen; Tantavisut, Saran (Chulalongkorn Medical Journal, 2026)
Background: Sarcopenia is an underrecognized condition that may impair recovery in older adults after hip fracture surgery. Objectives: This study aimed to assess the effect of sarcopenia on the functional outcomes and hip muscle strength in elderly individuals with femoral neck fractures while accounting for other potential confounding factors using a structural equation model (SEM). Methods: This prospective cohort study was conducted at a tertiary university hospital between January 2023 and October 2024, enrolling patients aged 60 years and older undergoing bipolar hemiarthroplasty for displaced femoral neck fractures. Functional recovery was evaluated at the 3-month follow-up using the Barthel Index (BI), Short Physical Performance Battery (SPPB), Harris Hip Score (HHS), and hip muscle strength. Sarcopenia was diagnosed per the 2019 Asian Working Group criteria, alongside assessments for osteoporosis and nutrition. SEM analyzed the effect of sarcopenia on recovery while adjusting for key factors. Results: Sixty patients (mean age: 81.0 ± 8.4 years; 76.7% female) were included, of whom 15 (25.0%) were identified as sarcopenic. Sarcopenia and malnutrition had substantial negative effects on the BI, HHS, and SPPB scores. Longer hospital stays were independently associated with lower HHS. SEM revealed indirect pathways that linked age, body mass index, and baseline functional status to outcomes via sarcopenia and malnutrition. Sarcopenia was notably associated with reduced hip muscle strength, as measured by a latent variable. Conclusion: Sarcopenia and malnutrition are major contributors to impaired short-term functional recovery after bipolar hemiarthroplasty in elderly patients with femoral neck fractures. Both factors affect the physical performance, hip-specific function, and independence in daily activities, independently and synergistically. The SEM highlighted the interrelationships between nutritional status, sarcopenia, and baseline function, emphasizing the importance of early detection and targeted interventions during postoperative care.